Preparation, Characterization and Physicochemical Behaviour of New Acetylated Schiff Base Ligand and its Metal Complexes - Naz, Narjis; Ajaz, Humayun; Sadiq, Zubi (Asian Journal of Chemistry, 2014)
We wish to report herein some new metal complexes of (S)-5-[(E)-3-(2-hydroxybenzylidene)guanidine]-2-acetamido pentanoic acid. Acetylation was successfully executed by the action of acetic anhydride on condensed product of salicylaldehyde and L-arginine named (S)-5-[(E)-3-(2-hydroxybenzylidene)guanidine]-2-amino pentanoic acid. Bidentate ligand was coordinated with Ni(II), Fe(II), Cr(III), Mn(II), Zn(II) and Cu(II) salts to furnish their respective metal complexes. FTIR, UV-visible. and MS spectrum of ligand and metal complexes were studied. TGA analysis showed thermal properties of compounds while their crystal systems were proved by X-ray diffraction technique. The results suggested that the ligand is bonded to metal through hydroxyl oxygen and the imino nitrogen.